FRI0519 Ultrasound Definition of Cartilage Change in Patients with Rheumatoid Arthritis: A Reliability Study by The Omeract Ultrasonography. (15th July 2016) - Mandl, P.; Filippucci, E.; Alasti, F.; Bachta, A.; Backhaus, M.; Bong, D.; Bruyn, G.A.; Collado, P.; Damjanov, N.; Dejaco, C.; Delle-Sedie, A.; Duftner, C.; et al.
Abstract : Objectives: To produce ultrasound (US) consensus-based definitions of cartilage change in rheumatoid arthritis (RA) and assess its intraobserver and interobserver reliability in a web-based exercise. Methods: We conducted a Delphi study on US defined cartilage change and a proposed semiquantitative (SQ) US scoring system for cartilage change in RA. A written Delphi questionnaire was developed based on a systematic literature review and expert international consensus and was distributed via consecutive written questionnaires by email to a group 35 rheumatologists from 17 countries with experience in musculoskeletal US. Taskforce members performed US B mode examination of the metacarpal cartilage in metacarpophalangeal joints 2–5 in RA patients and the images were collected in an electronic database. A reference image atlas of cartilage changes was developed for scoring 123 anonymized images including 25 duplicate images. These were sent to the participants who independently scored the images. Intraobserver reliability was assessed by Cohen's kappa and interobserver reliability by Fleiss' kappa. Results: Group agreement (76–100%) was reached for 6 statements concerning: i) MSUS definition and assessment of normal hyaline cartilage, ii) elementary cartilage lesions in MSUS and iii) grading of elementary cartilage lesions in patients with RA in a two-round Delphi consensus process. A three-grade SQ (0–2) scoring system (grade 0, normal cartilage; grade 1, minimal change: blurring of outer and/or subchondral margin, focal thinning or incomplete loss of homogeneity of echostructure; grade 2, severe: diffuse thinning or complete loss of homogeneity of echostructure) was agreed for scoring cartilage damage in RA. Both intra- and inter-observer reliability were good (κ value of 0.87 and 0.64 respectively). Conclusions: This study demonstrates that US is a reliable tool for evaluating cartilage in RA and strongly supports the use of a new reliable semiquantitative MSUS scoring system for cartilage change. Disclosure of Interest: None declared